Profile of the impact on the oral health of persons with Parkinson’s disease during the COVID-19 isolation - de SOUZA, Hellen Kevillyn Brito; de OLIVEIRA, Jonatas Silva [UNESP]; da SILVA, Crislayne Felix; Coriolano, Maria das Graças Wanderley de Sales; Lins, Carla Cabral Dos Santos Accioly (FapUNIFESP (SciELO), 2023)
Introduction: the Covid-19 pandemic impacted elderly persons with Parkinson’s Disease (PD), influencing their daily activities and quality of life. Objective: to evaluate the impact on the oral health in people with Parkinson’s Disease during the Covid-19 isolation. Material and method: the present analytical, quantitative, cross-sectional study uses secondary data sources from 115 health records used in a study carried out from August to December in 2020 through telemonitoring. Sociodemographic aspects and self-perception of quality of life were evaluated using the Oral Health Impact Profile (OHIP-14) questionnaire. The variables studied in the association were: sex, age, duration of PD, civil status, Covid-19 diagnosis and the use of dental prostheses. The software Statistica 13.2 and the Chi-square (X2) test with a significance level of p<0.05 were used. Result: after analyzing the database, the final sample consisted of 64 health records that responded to the OHIP-14. 61% were male, with a mean age of 66.6 years, 64% were using dental prostheses, and 74% indicated on the OHIP-14 that they had good oral health self-perception. No significant associations were found among the variables: Age, Sex, Civil Status, Covid diagnosis, Duration of illness, Use of dental prostheses and the OHIP-14 (p>0.05). Conclusion: it was found that people with Parkinson’s Disease showed a good quality of life, as evaluated using the OHIP-14, and that the Covid-19 isolation did not impact negatively on the oral health.
Perfil do impacto da saúde bucal de pessoas com Parkinson durante o isolamento da COVID-19
Keywords: Covid-19; oral health; Parkinson’s disease; quality of life